MiR‐29b Downregulates Canonical Wnt Signaling by Suppressing Coactivators of β‐Catenin in Human Colorectal Cancer Cells. Issue 11 (November 2014) - Subramanian, Maitreyi; Rao, Srinivasa R.; Thacker, Pooja; Chatterjee, Suvro; Karunagaran, Devarajan
Abstract The β‐catenin/Wnt signaling pathway is activated in many cancers and its constitutive activation has a central role in colorectal cancer pathogenesis. Recent studies have highlighted the role of microRNAs as novel regulators of gene expression including that of signaling intermediates from the Wnt signaling pathway. The purpose of our study was to determine the role of miR‐29b in the regulation of Wnt signaling in human colorectal cancer cells. TOPFlash/FOPFlash reporter assays, gene expression studies by quantitative RT‐PCR and western blot analysis were used to study the effect of ectopic expression of miR‐29b on canonical Wnt signaling. miR‐29b antagonized transactivation of β‐catenin target genes by downregulating coactivators of β‐catenin (TCF7L2, Snail, and BCL9L) in SW480 cells. miR‐29b targeted the 3′UTR of BCL9L and decreased its expression with a consequent decrease in nuclear translocation of β‐catenin. Ectopic expression of miR‐29b inhibited anchorage independent cell growth, promoted reversal of epithelial to mesenchymal transition and reduced the ability of conditioned medium from SW480 cells to induce in vitro tube formation in endothelial cells. These results have unraveled a novel role of miR‐29b in Wnt signaling in human colorectal cancer cells with implications in the treatment of colorectal cancer. J. Cell. Biochem. 115: 1974–1984, 2014. © 2014 Wiley Periodicals, Inc.